The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12870-022-03715-5
|View full text |Cite
|
Sign up to set email alerts
|

Plastome comparison and phylogenomics of Fagopyrum (Polygonaceae): insights into sequence differences between Fagopyrum and its related taxa

Abstract: Background Fagopyrum (Polygonaceae) is a small plant lineage comprised of more than fifteen economically and medicinally important species. However, the phylogenetic relationships of the genus are not well explored, and the characteristics of Fagopyrum chloroplast genomes (plastomes) remain poorly understood so far. It restricts the comprehension of species diversity in Fagopyrum. Therefore, a comparative plastome analysis and comprehensive phylogenomic analyses are required to reveal the taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 66 publications
(100 reference statements)
2
13
0
Order By: Relevance
“…Zhang et al [ 55 ] adopted plastid phylogenomics to reveal the deep phylogenetic relationships and diversification history of Rosaceae. Li et al [ 56 ] also reported that phylogenomic analyses of Fagopyrum supported the division of the cymosum and urophyllum groups, and resolved the systematic position of subclades within the urophyllum group. However, it should be noted that plastid genomes could enhance species discrimination and reveal phylogeny, but they are still not powerful enough to resolve all species in complicated genera and recently diverged lineages, such as Paris , Berberis , and Rhododendron [ 26 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 55 ] adopted plastid phylogenomics to reveal the deep phylogenetic relationships and diversification history of Rosaceae. Li et al [ 56 ] also reported that phylogenomic analyses of Fagopyrum supported the division of the cymosum and urophyllum groups, and resolved the systematic position of subclades within the urophyllum group. However, it should be noted that plastid genomes could enhance species discrimination and reveal phylogeny, but they are still not powerful enough to resolve all species in complicated genera and recently diverged lineages, such as Paris , Berberis , and Rhododendron [ 26 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al [ 1 ] compared the plastomes of eight Fagopyrum species to determine sequence differentiation, repeat content, and the phylogeny of these species. Further building on previous studies Li et al [ 6 ] analyzed 12 plastomes of Fagopyrum and 49 plastomes from other genera in Polygonaceae demonstrating the utility of this type of data in resolving relationships at multiple taxonomic levels. In addition to these studies in Fagopyrum , several studies have shown that using a pan-genome approach to analyze plastome DNA sequences can provide useful insights into the origin and diversity of domesticated crops at the population level [ 29 ].…”
Section: Introductionmentioning
confidence: 88%
“…The cultivation of buckwheat can be traced back to about 4000 years ago [ 2 , 5 ]. The Fagopyrum genus contains about 15 to 28 species [ 6 ] of which only three are cultivated. The cultivated species are Fagopyrum esculentum (common buckwheat or sweet buckwheat) which is widely cultivated in Asia, Europe, and the Americas, while F. tataricum (Tartary buckwheat) and F. dibotrys (golden buckwheat) are mainly cultivated in China [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations